Intra-Host Evolution of Norovirus GII.4 in a Chronic Infected Patient With Hematopoietic Stem Cell Transplantation - Yu, Jie-mei; Liang, Ze-yin; Guo, Ke; Sun, Xiao-man; Zhang, Qing; Dong, Yu-jun; Duan, Zhao-jun (Frontiers in Microbiology, 2020)
Human noroviruses (NVs) are the leading cause of acute gastroenteritis outbreaks worldwide. The majority of outbreaks are caused by genogroup II.4 (GII.4), with new variants emerging every 2 to 4 years. Immunocompromised patients are hypothesized to be important reservoirs where new NV variants emerge. Here, we examined intra-host NV variants and assessed immune-driven NV evolution in chronically infected immunocompromised hosts. Three NV GII.4-positive samples were collected from the same patient in different clinical phases following allogeneic hematopoietic stem cell transplantation, and had viral RNA concentrations of 2.46×106, 1.47×106, and 2.26×106 genome copies/mL. The non-synonymous (dN) and synonymous (dS) substitution ratio of the sequences in the partial P domain were >1, indicating strong positive selection in the patient. Both the number and the frequency of the single nucleotide variants increased over time in the patient. Also, the majority of capsid amino acid changes were located at blocking epitopes and histo-blood group antigen (HBGA)-binding sites, and 11 positive selection sites were found in the capsid region, of which 8 sites were presented in blocking epitopes or HBGA-bingding sites. Homodimeric P-domain capsid models also suggested a structural change in the epitopes and HBGA-binding sites. The results suggested that novel variants of NV GII.4 with HBGA and antigenic site changes were produced in the immunocompromised patient. Further functional and epidemiological studies are needed to determine whether the new variants are a risk to public health.